What can be learned about gambling from a learning perspective? A narrative review. Issue 4 (2nd October 2019) - Ramnerö, Jonas; Molander, Olof; Lindner, Philip; Carlbring, Per
Abstract: Gambling is a field that harbors both harmless recreational activities and pathological varieties that may be considered an addictive disorder. It is also a field that deserves special interest from a learning theoretical perspective, since pathological gambling represents both a pure behavioral addiction involving no ingestion of substances and behavior that exhibits extreme resistance to extinction. As the field of applied psychology of learning, or behavior analysis, espouses a bottom-up approach, the basis of understanding begins in basic research on behavioral principles. This article provides a narrative review of the field of laboratory experiments conducted to disentangle the learning processes of gambling behavior. The purpose of this review is to give an overview of learning principles in gambling that has been demonstrated under lab conditions and that may be of importance in the development of clinical applications when gambling has become a problem. Several processes, like the importance of delay and probability discounting, reinforcement without actual winning, and rule governed behavior have been experimentally verified. The common denominator appears to be that they impede extinction. Other areas, especially Pavlovian conditioning, are scarce in the literature. Our recommendations for the future would be to study Pavlovian and instrumental conditioning in interaction. Treatment programs should profit from strategies that serve to enhance extinction learning. We also conclude that online gambling should provide a promising environment for controlled research on how to limit excessive gambling, provided that the gambling companies are interested in that.